Should I Signal Trust? Effect of Terrorism on Interpersonal Trust in Post-Conflict and Non-Post-Conflict Countries - Phayal, Anup (Terrorism and political violence, 2023)
Generalized interpersonal trust is an essential component of a functioning society. While some studies have examined how the perception of terrorism affects trust, cross-national works investigating the impact of actual terrorist attacks on individual trust remain mixed. In this paper, I use insights from existing studies to disaggregate generalized interpersonal trust in response to terrorism in two distinct dimensions, prosocial motivation, and strategic signaling. While threat perception from terrorism lowers interpersonal trust in all contexts, I argue that actual events distinctively shape a person’s interpersonal trust. In a relatively stable and secure context of a non-post-conflict country, individuals living closer to terrorist incidents express increased interpersonal trust. But in post-conflict countries, those closer to terrorist incidents tend to show more distrust. To test the argument, I use the World Values Survey dataset of fifty-two states and create a terrorism scale for 717 survey regions within the countries, considering their spatial and temporal closeness to each terrorist incident. Results obtained from three-level hierarchical models (state, region, and individual) are robust and contribute to our understanding of how terrorism shapes interpersonal trust in different contexts.